A comparative analysis of NFHS-4 and 5 household profile indicators in districts of Haryana, India - Ohlan, Sunny; Singh, Sandeep; Singhal, Parul; Goyal, Rakhi; Goyal, Antim (International Journal Of Community Medicine And Public Health, 2022)
National family health survey is a large scale, multi-round survey conducted in a representative sample of households throughout India. Till date there are five rounds of the NFHS surveys were conducted starting from NFHS-1 in 1992-93 followed by NFHS-2 in 1998-99 after that NFHS-3 in 2005-06, then NFHS-4 in 2015-16 and lastly and recently conducted NFHS-5 from 2019 to 2021. NFHS - 5 has been captured during 2019-20 and has been conducted in around 6.1 lakh households. The international institute for population sciences Mumbai, served as the nodal organization providing coordination and technical guidance for the NFHS. In order to monitor the ongoing health and family welfare programs in between two census, NFHS is being undertaken. Household’s profile indicators of NFHS-4 and 5 in this article comprised of improved sanitation facility, improved drinking water source, using iodized salt, coverage under a health insurance, a household with electricity and using clean fuel for cooking. The comparison will help in understanding where the policy and program makers need to be more focused as per administrative division of the state and area of household profile, in collaboration with National health programs and policies.